Phytochemicals of Salvia africana, Salvia elegans and Salvia officinalis 'Icterina' - Fernandes Afonso, Andrea Luísa (2018)
Salvia species are used worldwide for medicine purposes. In general, these medicinal plants have high amounts of flavonoids and phenolic acids that are generally accepted to be closely related to their health properties [1,2]. Albeit that, the phenolic composition of many Salvia species remains unclear. In this work, S. africana, S. elegans and S. officinalis 'Icterina' aqueous extracts were prepared by decoction and analysed by high performance liquid chromatography with diode array detector coupled to an electrospray ionization mass spectrometer (UHPLC-DAD-ESI-MSn), in order to identify their main phenolic constituents. The extracts from the three Salvia species were mainly rich in rosmarinic acid (UVmax 290, 328 nm) and in the flavone luteolin-O-glucuronide (MW 462; UVmax 250, 267, 345 nm). In addition to these two, danshensu, a caffeic acid derivative ([M-H]− at m/z 197→179, UVmax 280 nm), was detected in S. africana and S. officinalis 'Icterina', while lithospermic acid B ([M-H]− at m/z 717→ 519, 475, 537, UVmax 290, 337 nm) was found in S. elegans. In turn, the yunnaneic acid D ([M-H]− at m/z 539→297, 359, 179, UVmax 270 nm), 3′-O-(8″-Z-caffeoyl) rosmarinic acid and salvianolic acid K (MW 556) were exclusively detected in S. africana, S. elegans and S. officinalis 'Icterina' extracts, respectively. Overall, this study contributed for the deepening of phytochemical knowledge of these three Salvia species.